Artificial Intelligence in Education - Katmer, Vildan; Demircioğlu, Aytekin (IGI Global Scientific Publishing, 2025)
The rapid development of artificial intelligence (AI) technologies are bringing about fundamental transformations in the field of education. This chapter, comprehensively examines the transformative impact of AI on educational curricula. The study begins by presenting an overview of AI in education, then proceeds to analyze in detail the role and contributions of this technology in pedagogical processes. The chapter presents strategies for integrating AI into curricula across different educational levels. New skills and competencies that students and educators need to acquire in the age of AI, such as digital literacy, AI literacy, and critical thinking, are elaborated upon. The study also addresses the challenges and limitations associated with the use of artificial intelligence in education, including ethical concerns, data privacy issues, digital divide, and technological competencies of educators. In conclusion, this chapter highlights the potential of AI to transform curricula while emphasizing the importance of effectively integrating technology and pedagogy.